Valorización de los residuos de la industria cervecera para utilización como biosorbente. - Aldana, Carolina Estefania Duque (Universidade Federal de São Carlos, 2018)
The high costs of removing heavy metals and their toxic compounds has in recent decades, led to the demand for new and more efficient methods that are not only able to be removed but also recycled and reused since many of these metals have important industrial applications. In this search for sustainability, research has been done about the use of agricultural waste as absorbent, these lignocellulosic materials were found to be effective adsorbents of metal ions, which, chemically modified in most cases, increase their adsorption capacity. The present work used the two main residues of the brewing industry as a biosorbent: the barley bagasse biomass in three different sizes C80, C200 and C250 μm, and the biomass of Saccharomyces cerevisiae, FUS05. The SEM/EDS and FTIR analysis showed the rough texture of the samples and the presences of hydroxyl groups, alcohols groups, some methyl aliphatic groups, and amino bands on the material, respectively. However, the FTIR analysis after adsorption did not show significant changes in the functional groups. The data of Cu removal using C250 and FUS05 particles were found the best fit for a pseudo-second order while using the C80 and C200 particles did not show a good fit in either of the two kinetic models used (pseudo-first and pseudo-second order). Regarding the equilibrium study, the data were found best fit both C80 and C200 particles to Freundlich model and the biomass of S. cerevisiae was better adjusted to the Langmuir model, thus ordering the material according to its level of efficiency was found: FUS05> C80> C200> C250. These results demonstrate the potential of this material as a biosorbent of Cu (II) ions in solution. Finally, in terms of the material's applicability, the C80 particle was used in an artificial effluent, getting a copper removal higher than 50% although the experimental data were not fitted to any kinetic model under study.
Valorization of brewery waste material using as biosorbent
Keywords: Biomassa; Biossorção; Resíduos cervejeiros; Cobre; Sustentabilidade; Biomass; Biosoption; Brewery waste; Copper; Sustainability; OUTROS::CIENCIAS